Parental Response to Early Human Capital Shocks: Evidence from the Chernobyl Accident - Martin Halla; Martina Zweimüller (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2014)
Little is known about the response behavior of parents whose children are exposed to an early-life shock. In this paper we interpret the prenatal exposure of the Austrian 1986 cohort to radioactive fallout from the Chernobyl accident as a negative human capital shock and examine their parents response behavior. To identify causal effects we can rely on exogenous variation in the exposure to radioactive fallout (over time and) between communities due to geographic differences in precipitation at the time of the accident. We find robust empirical evidence of compensating investment behavior by parents in response to the shock. Families with low socioeconomic status reduced their family size, while families with higher socioeconomic status responded with reduced maternal labor supply. Compensating investment made by the latter group seems relatively more effective because we do not find any detrimental long-term effects for exposed children from higher socioeconomic backgrounds. In contrast, exposed children from low socioeconomic backgrounds have significantly worse labor market outcomes as young adults.
Keywords: I18; I20; Q48; Q53; J24; 330; Fetal origins; parental response; Chernobyl; radiation; health; culling; human capital; fertility; labor supply